Direct Observation of Reductive Coupling Mechanism between Oxygen and Iron/Nickel in Cobalt‐Free Li‐Rich Cathode Material: An in Operando X‐Ray Absorption Spectroscopy Study. Issue 24 (12th May 2021) - Dixon, Ditty; Mangold, Stefan; Knapp, Michael; Ehrenberg, Helmut; Bhaskar, Aiswarya
Abstract: Li‐rich cathodes possess high capacity and are promising candidates in next‐generation high‐energy density Li‐ion batteries. This high capacity is partly attributed to its poorly understood oxygen‐redox activity. The present Li‐rich cathodes contain expensive and environmentally‐incompatible cobalt as a main transition metal. In this work, cobalt‐free, iron‐containing Li‐rich cathode material (nominal composition Li1.2 Mn0.56 Ni0.16 Fe0.08 O2 ) is synthesized, which exhibits excellent discharge capacity (≈250 mAh g −1 ) and cycling stability. In operando, X‐ray absorption spectroscopy at Mn, Fe, and Ni K edges reveals its electrochemical mechanism. X‐ray absorption near edge structure (XANES) features of Fe and Ni K edges show unusual behavior: when an electrode is charged to 4.5 V, Fe and Ni K edges' XANES features shift to higher energies, evidence for Fe 3+ →Fe 4+ and Ni 2+ →Ni 4+ oxidation. However, when charged above 4.5 V, XANES features of Fe and Ni K edges shift back to lower energies, indicating Fe 4+ →Fe 3+ and Ni 4+ →Ni 3+ reduction. This behavior can be linked to a reductive coupling mechanism between oxygen and Fe/Ni. Though this mechanism is observed in Fe‐containing Li‐rich materials, the only electrochemically active metal in such cases is Fe. Li1.2 Mn0.56 Ni0.16 Fe0.08 O2 has multiple electrochemically active metal ions; Fe and Ni, which are investigated simultaneously and the obtained results will assist tailoring of cost‐effective Li‐rich materials. Abstract : A cobalt‐free Li‐rich cathode material in which Ni and Fe are electrochemically active is synthesized and its electrochemical reaction mechanism is investigated using in operando X‐Ray Absorption Spectroscopy. Both Ni and Fe in the material are found to undergo reductive coupling with oxygen, during charging above 4.5 V versus Li + /Li, contributing to the anomalous capacity observed in the first charge.